Strategi guru dalam meningkatkan kemampuan literasi membaca siswa - SOLEHA, FATIKA AINIS (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze teachers’ strategies in improving students’ reading literacy skills at the elementary school or Madrasah Ibtidaiyah level. Reading literacy is an essential skill that not only involves the ability to recognize words but also to understand, interpret, and evaluate information from texts. Low reading literacy skills among students have become a major obstacle to achieving academic success and personal development. This study employs a literature review approach by analyzing various literatures and previous studies regarding teachers’ strategies in reading literacy. The findings indicate that effective teacher strategies include the implementation of interactive learning, utilization of varied reading media, project-based learning, shared reading, group discussions, differentiated instruction, positive reinforcement, and the use of technology. These strategies are able to foster reading interest, enhance motivation, develop critical thinking skills, and cultivate sustainable reading habits. Regular evaluation is crucial for adjusting strategies and ensuring the optimal development of reading literacy. This study concludes that teachers play a central role in guiding students to master reading literacy. The study recommends the development of creative and adaptive teaching strategies, as well as the utilization of both print and digital media to create engaging, effective, and enjoyable reading experiences for students.